Counseling an alcohol abuse patient - Zh. V. Maksimova; D. M. Maksimov (Кардиоваскулярная терапия и профилактика, 2021)
Alcohol abuse is the regular or episodical alcohol consumption that can cause adverse medical and social consequences without signs of dependence. In Russia, 35% of the population regularly consume alcoholic drinks in very high doses. At the same time, abuse often remains undiagnosed or is not considered a medical problem. However, it is precisely this that causes the massive prevalence of alcohol-related physical and mental health problems, as well as social functioning. The situation can be improved, including through early detection and effective behavioral counseling, especially in primary health care. The World Health Organization recommends a five-step approach to identify and correct alcohol abuse:— identify the alcohol consumption level using the Alcohol Use Disorders Identification Test (AUDIT);— recommend decreasing alcohol consumption;— assess readiness and barriers to cessation or decrease of alcohol use;— help the patient to develop motivations;— continue monitoring and support on follow-up visits.Behavioral counseling for alcohol abuse is provided in a non-judgmental manner as part of the routine medical appointment for any other medical condition. The content of the counseling depends on the motivation of a patient. For hesitant patients who are uncertain about the appropriateness or their ability to reduce alcohol use, a so-called motivational interviewing is conducted, which allows a patient to speak out about the problem and helps to correct unhealthy behaviors. This article is a guideline for health care professionals on brief preventive counseling for alcohol abuse patients.